Burnout dan Kesejahteraan Psikologis Guru serta Dampaknya pada Motivasi Belajar Siswa: Perspektif dari Tinjauan Literatur - Saryani, Diaz; Harmathilda, Harmathilda; Sujai'i, Ahmad (Merpsy Journal, 2025)
The psychological well-being of a teacher is a vital element in creating a positive learning environment, and is related to performance. When teachers are in good psychological condition, they will develop more positively, be more optimistic when teaching, and be more able to adopt various innovative learning methods. The role of a teacher requires them to possess specific competencies, including preparing teaching materials, designing learning syllabi, delivering knowledge to students, evaluating student academic performance, enforcing discipline in classroom management, motivating students to learn, and many other skills. This research examines the psychological well-being of teachers in Indonesia in the context of efforts to enhance students' learning motivation. It employs a qualitative research method using a literature study approach. The aim of this research is to analyze the psychological impacts experienced by teachers in relation to student learning motivation at both primary and secondary education levels. The research findings indicate that individuals who possess emotional balance, a sense of purpose, and happiness are more capable of influencing students' learning motivation effectively. Reducing stress and life burdens on teachers—thus improving their psychological well-being—leads to the development of high-quality teachers, not only enhancing their professional lives but also significantly contributing to the achievement of optimal student learning outcomes.